Poder/saber e subjetividade na construção do sentido do teletrabalho - Costa, Isabel de Sá Affonso da (2003)
This thesis aims at fostering understanding of telework from the power/knowledge theoretical perspective. In this sense, telework is understood as a discourse that at one and the same time subjugates and builds subjectivities. To reach its objective, the author explores how teleworkers make sense out of their experience through the analysis of their discursive practices. Twenty-five teleworkers residing in Rio de Janeiro city were interviewed. All of the interviewees are teleworkers who hold stead job positions and perform knowledge- intensive tasks.